GROUND MOTION ATTENUATION EQUATION FOR EARTHQUAKE EVENTS IN THE SUBDUCTION ZONE OF SUMATRA - Faradila, Salsa Ayu; Putra, Rusnardi Rahmat (Teknik Sipil Universitas Negeri Padang, 2023)
The Sumatra subduction zone is a seismically active region due to the subduction of the Indo-Australian and Eurasian tectonic plates. The purpose of this research is to determine the ground motion attenuation equation based on earthquake records that have occurred in the Sumatra subduction zone. Ground acceleration data from earthquakes obtained from accelerographs between 2008 and 2018 were used. From the collection of ground acceleration data, 101 earthquake events with 150 ground acceleration data were obtained. The ground acceleration data were adjusted to match the earthquake events to obtain earthquake source parameters. Through multiple linear regression analysis, the attenuation equation for earthquake events in the Sumatra subduction zone was obtained as Log PGA = 3.3501 - 1.6217LogRh + 0.181Mw + 0.1321, where PGA represents the maximum ground acceleration, Rh represents the hypocenter distance, and Mw represents the moment magnitude. Compared to several other attenuation equations, this attenuation equation is relatively good and closely approximates the observed PGA results with a relatively strong correlation level of 0.785 and a small error level of 0.437.